Self-efficacy and support from family self-care for individuals with high blood pressure - Chrismilasari, Lucia Andi; Nursery, Septi Machelia Champaca; Candra Kusuma Negara (Sean Institute, 2024)
Hypertension is an abnormal and ongoing rise in blood pressure recorded more than once. The purpose of this study is to ascertain how family support and self-efficacy in managing one's hypertension relate to one another. This study used a cross-sectional research design with 245 participants. According to the study, those with high self-efficacy also typically had effective self-management (64.2 %). Regarding poor self-management, the dominant group is less adept at it (57.2 %). The dominant person in the excellent family support variable exhibits good self-management (61.1 %). Less family support results in poorer self-management for the dominating group (57.1 %). According to the chi-square test results, self-efficacy (p-value=0.006) and family support (p-value=0.001) are connected to self-management. In conclusion, patients with hypertension tend to control their condition better themselves if they have strong self-efficacy and family support.